1993
DOI: 10.1021/bi00080a021
|View full text |Cite
|
Sign up to set email alerts
|

Redox potentials of active-site bis(cysteinyl) fragments of thiol-protein oxidoreductases

Abstract: The active sites of thiol-protein oxidoreductases consist of the characteristic Cys-X-X-Cys motif, and the redox potentials of these enzymes reflect the propensity of the bis(cysteinyl) sequence portion for disulfide loop formation. Thereby, as is known from comparing the three-dimensional (3D) structures of thioredoxin and glutaredoxin in the reduced and oxidized state, reduction of the disulfide bond is accompanied by minimal perturbation of the backbone folding of the active sites. In order to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 40 publications
2
54
1
3
Order By: Relevance
“…Indeed, the disruption of the bridge by mutagenesis modified notably Nox4 ROS production [43]. Disulfide bridges with a standard redox potential (E 0 ) of À180 mV [47] could be reduced by NADPH, NADH and b-mercaptoethanol that possess a lower E 0 (À324, À320, and À253 mV, respectively) [48]. Our results using those reducing agents indicated that Nox4 activity could be stimulated by extracellular redox modifications, possibly through the reduction of its disulfide bridge.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, the disruption of the bridge by mutagenesis modified notably Nox4 ROS production [43]. Disulfide bridges with a standard redox potential (E 0 ) of À180 mV [47] could be reduced by NADPH, NADH and b-mercaptoethanol that possess a lower E 0 (À324, À320, and À253 mV, respectively) [48]. Our results using those reducing agents indicated that Nox4 activity could be stimulated by extracellular redox modifications, possibly through the reduction of its disulfide bridge.…”
Section: Discussionmentioning
confidence: 76%
“…Disulfide bonds in proteins have a free energy of Ϸ2-5 kcal/mol (26,27). The electrical free energy gained by movement of an S4 voltage sensor with three positive charges through an electrical potential of Ϫ200 mV is 13.8 kcal/mol (see SI Text for calculations of the energy and force of voltage sensor movement).…”
Section: Resultsmentioning
confidence: 99%
“…Disulfide cross-linking strategies have proven to be a powerful tool to analyze the structures of the intermediates in protein folding reactions and of intermediate and fully activated states in enzymes (21)(22)(23). We previously demonstrated using a disulfide-locking method that the third gating charge (R3) in the S4 segment of NaChBac forms an ion pair with D60 near the extracellular end of the S2 segment (24).…”
mentioning
confidence: 99%